2015
DOI: 10.1002/fsn3.219
|View full text |Cite
|
Sign up to set email alerts
|

Study on the extraction and purification of glycoprotein from the yellow seahorse, Hippocampus kuda Bleeker

Abstract: The optimum parameters of extraction for glycoprotein from seahorse were examined and determined by Box-Behnken combined with ultrasonic extraction technology. Column chromatography of glycoprotein was used for further purification. The optimal extraction conditions of seahorse glycoprotein were extracting time 4.3 h, salt concentration 0.08 mol/L, extracting temperature 73°C, raw material, and water ratio 1:6. At the optimal conditions, the yield of saccharide reached to 1.123%, and the yield of protein reach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…Senyawa bioaktif yang biasa terdapat dalam bahan aktif adalah senyawa metabolit sekunder dan metabolit primer (Kumaravel et al, 2015). Beberapa manfaat yang dimiliki kuda laut tersebut, sehingga masyarakat dapat memanfaatkan khasiatnya sebagai alternatif dalam pengobatan secara alami (Su and Xu, 2015). Manfaat lain dari kuda laut salah satunya sebagai sumber makanan protein hewani yang banyak gizi dan sangat baik dikonsumsi oleh manusia.…”
Section: Pendahuluanunclassified
“…Senyawa bioaktif yang biasa terdapat dalam bahan aktif adalah senyawa metabolit sekunder dan metabolit primer (Kumaravel et al, 2015). Beberapa manfaat yang dimiliki kuda laut tersebut, sehingga masyarakat dapat memanfaatkan khasiatnya sebagai alternatif dalam pengobatan secara alami (Su and Xu, 2015). Manfaat lain dari kuda laut salah satunya sebagai sumber makanan protein hewani yang banyak gizi dan sangat baik dikonsumsi oleh manusia.…”
Section: Pendahuluanunclassified
“…After being extracted and purified using solid phase extraction (SPE) technology, the samples were analyzed by hydrophilic interaction liquid chromatography (HILIC) coupled with Q-TOF-MS, and 50 kinds of phospholipid molecules were isolated and identified, including 15 kinds of PCs, 14 kinds of PEs, 12 kinds of PIs and nine kinds PSs. Su & Xu (2015) extracted the fatty acids from Hippocampus by CO 2 supercritical fluid extraction technique, and the composition and distribution of fatty acids were determined by gas chromatography-mass spectrometry (GC–MS). Huang & Xu (2016) compared the extraction efficiency of fatty acids from Hippocampus under different extraction methods, and analyzed their fatty acid composition by GC–MS.…”
Section: Chemical Constituentsmentioning
confidence: 99%
“…Pharmacological studies have shown that Hippocampus have anti-oxidation ( Chen et al, 2010 , Kim et al, 2019 , Zheng et al, 2012 ), anti-inflammation ( Chen et al, 2015 , Tharuka et al, 2019 , Wu et al, 2020 ), anti-depressant ( Li et al, 2020 ), anti-hypertension ( Je et al, 2020 ), anti-prostatic hyperplasia ( Xu et al, 2014 ), anti-virus ( Sandamalika et al, 2021 , Tharuka et al, 2019 , Udayantha et al, 2021 ), anti-apoptotic ( Kodagoda et al, 2022 , Sellaththurai et al, 2020 , Wijerathna et al, 2022 ), anti-fatigue ( Guo et al, 2017 , Zhang et al, 2019 ), and other functions ( Pangestuti et al, 2013 , Sellaththurai et al, 2020 , Yuan et al, 2018 ). And those pharmacological action are mainly related to their active ingredients, including amino acids ( Ge et al, 2019 , Sari et al, 2017 , Zhao, 2018 ), abundant proteins (peptides and oligopeptides) ( Je et al, 2020 , Pangestuti et al, 2013 ), fatty acids ( Huang & Xu, 2016 , Shen et al, 2016 , Su & Xu, 2015 ), nucleosides ( Wei et al, 2015 , Zhao et al, 2011 ), steroids ( Wu et al, 2017 , Zhao, 2018 ), and other small molecular compounds ( Si et al, 2018 , Zhao, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Glycoproteins of Hippocampus have rarely been reported because of their relatively complex composition. Box-Behnken and ultrasonic extraction technology were applied to separate glycoproteins HG-11 and HG-21 (Su and Xu, 2015a). Glycoproteins included in marine organisms are the main active ingredients and deserve additional attention in future research.…”
Section: Other Ingredientsmentioning
confidence: 99%